Upper and lower body power are strong predictors for selection of male junior national volleyball team players - Tsoukos, A.; Drikos, S.; Brown, L. E.; Sotiropoulos, K.; Veligekas, P.; and Bogdanis, G. C. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to determine whether a battery of anthropometric and lower and upper body strength and speed and power tests predicted selection of young volleyball players for a Junior National Team by expert coaches. Fifty-two male junior volleyball players (14.8 ± 0.5 years, height: 1.84 ± 0.05 m, body mass: 72.5 ± 7.1 kg) took part in a training camp and underwent a selection procedure by expert coaches' of the junior national team. Anthropometric data and fitness tests results were obtained and players were graded on a scale from 0 to 100 on the basis of their performance in a volleyball tournament. Selected players were superior in the majority of measured variables (p ? 0.017) and had higher grading scores compared with nonselected players (85.3 ± 4.1 vs. 70.5 ± 5.6, respectively, p < 0.01). The combination of spike jump and reach (SJR) test and 3-kg medicine ball throw (MB3) velocity explained 63.5% of the variance in expert coaches' grading (p < 0.001). A multivariate discriminant analysis yielded a significant discriminant function (Wilk's lambda = 0.55, X2 = 29.324, p < 0.001, X2 = 0.82). Spike jump and reach and MB3 were the only variables that contributed to the discriminant function (standardized function coefficients: SJR = 0.68, MB3 = 0.67). Cross-validation results showed that selection was correctly predicted in 14 of the 16 selected players (predictive accuracy: 87.5%) and in 32 of the 36 nonselected players (predictive accuracy: 88.9%). The SJR and MB3 fitness tests can predict a large portion of the variance of expert coaches' grading and successfully discriminate elite young male volleyball players for selection vs. nonselection for a junior national team. This result is very important as performance testing during a selection process may be reduced to only 2 measurements.